70. Changes in Invasive Pneumococcal Disease among Adults Living with HIV Following Introduction of 13-Valent Pneumococcal Conjugate Vaccine, 2008–2018. (4th December 2021) - Matanock, Almea; Li, Jianmin; Adih, William; Xing, Wei; Schaffner, William; Alden, Nisha B; Harrison, Lee; Petit, Susan; Baumbach, Joan; Reingold, Arthur; Almendares, Olivia; Gierke, Ryan; et al.
Abstract: Background: People living with HIV (PLHIV) are at increased risk of invasive pneumococcal disease (IPD). The 13-valent pneumococcal conjugate vaccine (PCV13) was recommended for children in 2010, and for immunocompromised adults (including PLHIV) in series with 23-valent polysaccharide vaccine (PPSV23) in 2012. We evaluated changes in IPD incidence in adults ≥ 19 years old by HIV status after PCV13 introduction and proportion of remaining IPD due to serotypes included in the 15- (PCV15) and 20-valent (PCV20) conjugate vaccines expected to be licensed in 2021. Methods: IPD cases were identified through CDC's Active Bacterial Core surveillance (ABCs). HIV status was obtained from medical records. Isolates were serotyped by Quellung reaction, or whole-genome sequencing and grouped into PCV13-types, PPV11-types (unique to PPSV23), or non-vaccine types. We estimated IPD incidence (cases per 100, 000 people) using national projections of ABCs cases as numerators and national case-based HIV surveillance (PLHIV) or US census data (non-PLHIV) as denominators. We compared IPD incidence in 2011–12 and 2017–18 to pre-PCV13 baseline (2008–09) by serotype groups. We assessed the proportion of IPD due to serotypes included in PCV15 and PCV20. Results: Overall IPD incidence at baseline was 306.7 for PLHIV and 15.2 for non-PLHIV. From baseline to 2017–18, IPD incidence declined in PLHIV (-40.3%; 95% CI: -47.7, -32.3%) and non-PLHIV (-28.2%; 95% CI: -30.9, -25.5%). The largest reductions were in PCV13-type IPD during both periods (-44.2% for PLHIV and -42.2% for non-PLHIV in 2011–12; -72.5% for PLHIV and -62.2% for non-PLHIV in 2017–18) compared to baseline (Figures 1, 2). In 2017–2018, overall IPD and PCV13-type rates were 16.8 (95% CI: 15.1, 18.5) and 12.6 (95% CI: 9.9, 15.3) times as high in PLHIV vs non-PLHIV, respectively; PCV13, PCV15/non-PCV13, and PCV20/non-PCV15 serotypes comprised 21.5%, 11.2% and 16.5% of IPD in PLHIV. IPD incidence rates among adults aged ≥19 years old by serotype group in PLHIV, 2008–2018 IPD incidence rates among adults aged ≥19 years old by serotype group in non-PLHIV, 2008–2018 Conclusion: IPD rates declined significantly in both PLHIV and non-PLHIV during the study period due to reductions in PCV13-type IPD; however, IPD rates remained 17-fold higher in PLHIV compared to non-PLHIV, mainly due to non-PCV13 types. Higher-valent pneumococcal conjugate vaccines provide opportunities to reduce some of the remaining IPD burden in PLHIV. Disclosures: William Schaffner, MD, VBI Vaccines (Consultant) Lee Harrison, MD, GSK, Merck, Pfizer, Sanofi Pasteur (Consultant)